Óleo essencial de eucalipto como bioestimulador da micorrização e do estabelecimento de mudas de eucalipto e sibipiruna em solo contaminado com cobre - Steffen, Ricardo Bemfica (2010)
Ectomycorrhizal fungi (fECM) combined with the plant root system improve the absorption of water and nutrients, providing great plant growth, especially in environments with nutritional deficiency or degraded. Due to the fECM and plants live in mutualistic association, allows the fungal symbionts to be benefit, or at least tolerate, the secondary metabolites produced by plants. It is possible that essential oils extracted from forest species that form mycorrhizal associations by stimulating the growth of ectomycorrhizal isolates and benefit the plant-fungus symbiosis. This study aimed to evaluate the effect of Eucalyptus grandis W. Hill ex. Maiden essential oil, the inoculum production of fECM and its influence on the tolerance of the isolates to heavy metals copper, zinc and nickel. Also, determines the effect of the use of essential oil on growth of eucalyptus (Eucalyptus grandis) and sibipiruna (Caesalpinia peltophoroides) seedlings in the greenhouse and the establishment of eucalyptus soil contaminated by copper under controlled conditions and field. The evaluation of the effect of different eucalyptus essential oil concentrations to stimulate the growth of fECM Pisolithus sp. (UFSC Pt 24 and UFSC Pt 188), Pisolithus microcarpus (UFSC Pt 116), Chondrogaster angustiporus (UFSC Ch 163), Scleroderma citrinum (UFSC Sc 124) and Suillus sp. (UFSM RA 2.2 and UFSM RA 2.8) in liquid culture medium MNM, allow to observe that the addition of eucalyptus essential oil concentrations 20 and 30 μL L-1 promoted an increase in mycelium growth in vitro of the isolates UFSC Pt 24, UFSC Pt 116, Ch 163 UFSC, UFSC Sc 124, UFSM RA 2.2 and UFSM RA 2.8. In liquid culture medium containing heavy metals copper, zinc and nickel. It was observed that the addition of essential oil at concentration of 20 μL L-1 increased the growth of ectomycorrhizal isolates. The evaluation of use of essential oil extracted from eucalyptus leaves on germination and initial development of eucalyptus seedlings in nursery conditions, permits to observe that germination was significantly highest when the seeds were sprayed with 25 μL L-1 oil essential. The application of essential oil at concentrations of 30 and 40 μL L-1 improve the development of roots and shoots of eucalyptus seedlings in a controlled environment. This can be an effective alternative in the biostimulation of the vegetative growth of eucalyptus seedlings. The effect of the use of essential oil was also positive when applied to eucalyptus seedlings inoculated 90 days after inoculation, improving both the mycorrhizal and seedling growth. Evaluating the effect of eucalyptus essential oil in the formation of ectomycorrhizal association and growth of sibipiruna seedlings after 90 days under greenhouse conditions. It was found that the application of essential oil enhanced the association of ectomycorrhizal fungus P. microcarpus and the development in seedlings of sibipiruna seedlings. The assessment of the degree of mycorrhizal association was determined by the percentage of mycorrhization. Eucalyptus seedlings grown in fertilized substrate, by using of essential oil in the formulation of inoculant or through subsequent application resulted in plants with highest height, fresh and dry weight, diameter and adaptability in soil contaminated by copper. These results may improve the establishment of mycorrhizal fungi in seedlings of sibipiruna seedlings as well as development and growth of eucalyptus seedlings in sites contaminated by heavy metals.